Sacred Iron and Celestial Birth: The Science, Culture, and Spirituality of Iron in Childbirth - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
This study explores the practice of placing iron objects near women during labor, examining its cultural, religious, and symbolic significance, along with potential scientific explanations. While the practice persists in various regions, its underlying mechanisms remain poorly understood. The study aims to investigate whether this practice has any scientific basis, its connection to spiritual beliefs, and its role in these rituals. A combination of qualitative methods, including semi-structured interviews, a review of papers, and relevant religious texts, was employed. Data were analyzed thematically, and comparisons were drawn across African, European, Latin American, Asian, and Chinese traditions. Findings suggest that the use of iron is often linked to beliefs in its protective qualities, symbolizing strength and divine assistance. Iron's capacity to protect mother and child from spiritual harm or outside threats is emphasized in cultural and religious contexts. The study found psychological processes, stress reduction, and placebo effects could support the ongoing practice of putting iron items close to women who are in labor. In conclusion, the activity has psychological and symbolic significance in addition to its strong traditional roots. It is advised that more research be done to determine the precise function of these customs and any possible medical advantages in delivery environments. Future studies should try to connect contemporary medical knowledge with cultural customs to offer a thorough comprehension of these rites.